PENINGKATAN SERVICE PERFORMANCE MELALUI TA’AWUN, RELIGIOSITY DAN MOOD - Wasitowati Wasitowati; Ken Sudarti (STIE Pelita Nusantara Semarang, 2019)
This study aims to investigate and test the role of ta'awun behavior in mediating between religiosity and mood. The questionnaire was distributed to 155 employees working in Islamic colleges. By using the PLS test, it was found that religiosity and mood influenced the behavior of ta'awun and ta’awun's behavior was able to improve service performance. With adequate literature studies, this study is able to enrich the repertoire of studies of variables related to human resource management that are sick with Islamic values. Conceptual discussion and empirical results also link the results of previous studies that included religious elements in managing human resources.